Evaluation from a gender perspective: learning from british and Swedish development cooperation systems - Espinosa-Fajardo, Julia (Iberoamerican Journal of Development Studies, 2014)
Gender equality was introduced into international development evaluation two decades ago. Over these years, there have been different experiences in incorporating gender issues into the evaluative exercises. In this paper, we analyze the evaluative experience of British and Swedish development cooperation systems –two of the most outstanding in relation to gender and evaluation- during the period 2000-2010 and we study how they have included gender equality in evaluation. We especially explore the incorporation of gender issues in their political commitment, evaluation procedures, methodologies and practices. And, according to this analysis, we present some learning in order to enlighten next evaluation exercises and to contribute to the improvement and accountability of the development cooperation policies.
Keywords: Evaluation; gender equality; development cooperation policies